2005
DOI: 10.1002/jbm.a.30347
|View full text |Cite
|
Sign up to set email alerts
|

Development of an infection‐resistant, bioactive wound dressing surface

Abstract: Trauma, whether caused by an accident or in an intentional manner, results in significant morbidity and mortality. The goal of this study was to develop a novel biomaterial surface in vitro and ex vivo that provides both localized infection resistance nd hemostatic properties. Our hypothesis is that a combination of specific surface characteristics can be successfully incorporated into a single biomaterial. Functional groups were created with woven Dacron (Cntrl) material via exposure to ethylenediamine (C-EDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…This results in reducing the durability of PET in implants and other long-term biomedical applications. Even with these limitations, many studies have demonstrated immobilization of active biomolecules [5,6,16,19,21,22,[24][25][26]. These studies have also showed improved hemocompatibility [6,19,21], infection resistance [5,[24][25][26] and cell adhesion [22].…”
Section: Introductionmentioning
confidence: 98%
“…This results in reducing the durability of PET in implants and other long-term biomedical applications. Even with these limitations, many studies have demonstrated immobilization of active biomolecules [5,6,16,19,21,22,[24][25][26]. These studies have also showed improved hemocompatibility [6,19,21], infection resistance [5,[24][25][26] and cell adhesion [22].…”
Section: Introductionmentioning
confidence: 98%
“…Following the pioneering work of Gagliardi [20], which described the principles and strategies for imparting antimicrobial activities into fibrous materials, various biocidal agents, including antibiotics [21][22][23], metal ions [24], quaternary ammonium salts [25][26][27], phosphonium compounds [27,28], N-halamines [29,30], etc., have been incorporated into fibrous materials. The antimicrobial activities and mechanisms of these agents differ considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the incidence of infection with gram‐negative ( Escherichia coli and Pseudomonas aeruginosa ) and gram‐positive bacteria ( Staphylococcus aureus ) in surgical wounds is increasing. These are common environmental contaminants of burn wounds and other skin traumas, and can cause sepsis following introduction via dressing fluids and other sources . Previous studies show that chitosan is a natural, cationic, biologically renewable, biocompatible, nontoxic, and biofunctional compound and that its antimicrobial activity against bacteria accelerates wound healing and improves tissue reorganization .…”
Section: Introductionmentioning
confidence: 99%
“…These are common environmental contaminants of burn wounds and other skin traumas, and can cause sepsis following introduction via dressing fluids and other sources. 22,23 Previous studies show that chitosan is a natural, cationic, biologically renewable, biocompatible, nontoxic, and biofunctional compound and that its antimicrobial activity against bacteria accelerates wound healing and improves tissue reorganization. 24,25 In the present study, we fabricated a wound dressing containing chitosan/g-PGA/pluronic/curcumin nanoparticles that were incorporated in a chitosan membrane.…”
Section: Introductionmentioning
confidence: 99%